1998
DOI: 10.1128/jb.180.14.3517-3521.1998
|View full text |Cite
|
Sign up to set email alerts
|

The apeE Gene of Salmonella typhimurium Encodes an Outer Membrane Esterase Not Present in Escherichia coli

Abstract: Salmonella typhimurium apeR mutations lead to overproduction of an outer membrane-associated N-acetyl phenylalanine β-naphthyl ester-cleaving esterase that is encoded by the apeE gene (P. Collin-Osdoby and C. G. Miller, Mol. Gen. Genet. 243:674–680, 1994). This paper reports the cloning and nucleotide sequencing of the S. typhimurium apeE gene as well as some properties of the esterase that it encodes. The predicted product of apeE is a 69.9-kDa protein which is processed to a 67-kDa species by removal of a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The deduced protein sequence of EstA does not exhibit the G-X-S-Y-G motif characteristically observed in eukaryotic and prokaryotic esterases and lipases (Cho and Cronan 1993;Jaeger et al 1994). Also, EstA does not have the G-D-S-L or G-D-S-L-S motifs which represent distinct subfamilies of serine-dependent esterases and lipases (Cho and Cronan 1993;Upton and Buckley 1995;Chang et al 1996;Carinato et al 1998). However, EstA does have a G-X-H motif located 22 residues from the COOH-terminus, which is characteristic of G-D-S-L and G-D-S-L-S type aryl-and thioesterases (Cho and Cronan 1993;Upton and Buckley 1995).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The deduced protein sequence of EstA does not exhibit the G-X-S-Y-G motif characteristically observed in eukaryotic and prokaryotic esterases and lipases (Cho and Cronan 1993;Jaeger et al 1994). Also, EstA does not have the G-D-S-L or G-D-S-L-S motifs which represent distinct subfamilies of serine-dependent esterases and lipases (Cho and Cronan 1993;Upton and Buckley 1995;Chang et al 1996;Carinato et al 1998). However, EstA does have a G-X-H motif located 22 residues from the COOH-terminus, which is characteristic of G-D-S-L and G-D-S-L-S type aryl-and thioesterases (Cho and Cronan 1993;Upton and Buckley 1995).…”
Section: Discussionmentioning
confidence: 94%
“…Alignment of amino acid residues surrounding S10 in EstA with those surrounding putative active-site serine residues from arylesterases, thioesterases and lipases from other sources (Table 4) revealed that EstA is different from the G-X-S-Y-G family and G-D-S-L and G-D-S-L-S subfamilies of esterases and lipases (Cho and Cronan 1993;Jaeger et al 1994;Upton and Buckley 1995;Chang et al 1996;Carinato et al 1998). However, the presence of an Ile residue instead of a Leu residue in position 4 of the G-D-S-L motif suggests that EstA may be more closely associated with the G-D-S-L subfamily of esterases and lipases.…”
Section: Discussionmentioning
confidence: 99%
“…EstA, the autotransporter esterase of P. aeruginosa , shows similarity to ApeE, an outer membrane esterase from S. enterica serovar typhimurium 30 and to Lip‐1, a lipase from Xenorhabdus (Photorhabdus) luminescens ,31 both of which are autotransporter proteins. Additional homologues include phospholipase B from Moraxella bovis ,32 McaP from Moraxella catharralis ,33 EstE from Xanthomonas vesicatoria 34 and EstA from Serratia liquefaciens MG135 (Table 1).…”
Section: Physiological Functions Of Gsdl Autotransportersmentioning
confidence: 99%
“…The mature autotransporter ApeE is a 67 kDa outer membrane esterase that catalyses the hydrolysis of a variety of fatty acid naphthyl esters, and of C6–C16 fatty acid p ‐nitrophenyl esters 30. This enzyme is also responsible for the hydrolysis of the substrate methylumbelliferyl caprylate (MUCAP); this is used in clinical laboratories to distinguish Salmonella strains from other clinically relevant bacteria 30.…”
Section: Physiological Functions Of Gsdl Autotransportersmentioning
confidence: 99%
See 1 more Smart Citation